Comparison of the scavenging intensity, remineralization and residence time of 210Po and 210Pb at key zones (biotic, sediment-water and hydrothermal) along the East Pacific GEOTRACES transect. (March 2019) - Niedermiller, John; Baskaran, Mark
Abstract: The contrasting geochemical behavior of two long-lived progeny of 222 Rn (daughter product of 226 Ra), 210 Po and 210 Pb, provide valuable insights on the extent of recycling of biogenic particulate matter and their preferential removal from the water column. We collected and analyzed 135 water samples from six vertical profiles for 210 Po and 210 Pb as well as a suite of aerosol samples for 210 Pb along the US GEOTRACES East Pacific Zonal Transect (GP16). Calculated atmospheric depositional flux of 210 Pb from the measured 210 Pb activity in aerosols exhibits an overall decrease from east to west along the cruise track. The inventories of 210 Po and 210 Pb and residence times in key zones that include biotic (upper 60 and 300 m), sediment-water (bottom 300 m) and volcanogenic (bottom 300 m at the East Pacific Rise (EPR) station) were calculated and compared. A comparison of inventories of 210 Po and 210 Pb in 500-m layers (maximum penetration depth of atmospherically-delivered 210 Pb was reported to be upper < 500 m) for all stations indicates clearly discernable disequilibrium between total (= particulate + dissolved) 210 Po and total 210 Pb, with 210 Po/ 210 Pb activity ratios less than 0.95 or greater than 1.05, in 63% (26 out of 41) of the 500-m layers. The observed large variations in the 210 Po/ 210 Pb activity ratio (AR) in 500 m layers (range: 0.79–1.32) of the whole water column is by far the largest disequilibrium in open ocean water reported when integrated over 500 m depths. However, the whole water-column 210 Po/ 210 Pb AR, calculated from the inventory of total 210 Po and total 210 Pb, varied between 0.97 ± 0.02 and 1.06 ± 0.02 (except in the EPR site, with 1.09 ± 0.02), indicating at or near-equilibrium for the whole water column in all five deep water stations. This contrasts with earlier claims of gross disequilibrium between 210 Po and 210 Pb in water depths >1000 m and we contend that most of these observations do not take in to account the variable extent of redistribution of 210 Po and 210 Pb in the water column due to remineralization of biogenic particulate matter and preferential scavenging of 210 Po over 210 Pb. We observed intense scavenging of 210 Po and 210 Pb in the bottom 300 m of the EPR site (attributed to discharge of high amounts of dissolved and colloidal Fe and Mn from the hydrothermal vent) and lower scavenging in the upper and bottom 300 m at the most oligotrophic station (ST-36), indicating that the scavenging intensities in bottom waters are likely coupled to the surface waters. Highlights: Wide-spread (64% of 500-m layers) 210 Po- 210 Pb disequilibrium in open ocean. For the whole water-column, 210 Po/ 210 Pb activity ratio >0.9 Redistribution of 210 Po and 210 Pb in the whole water column caused by remineralization. Coupling between scavenging of Po and Pb in upper and bottom 300 m of water column.